Investigation of Toxocariasis in Stray Dogs of Sanandaj, Western Iran - yahya Maroufi; ghasem zamini; Mohammad Bagher Khadem Erfan; Bijan nori; ashkan faridi (مجله علمی دانشگاه علوم پزشکی کردستان)
Abstract Background and Aim: Toxocariasis is a parasitic disease caused by the round worm Toxocara. Dogs are the definitive host for this parasite and, also several pathogens could be transmitted by dogs to humans as zoonotic diseases. Materials and Methods: This study was conducted in 2016-2017 with 111 stool samples collected from stray dogs in Sanandaj. Sanandaj was divided into five parts: north, south, east, west, and center. The coordinates of the sampling site were determined on the map by online GPS and ArcGIS software. Samples were examined by formalin-ether concentration method. The rate of toxocariasis in dogs was obtained by descriptive statistical methods and expressed as a percentage. Results: Out of 111 samples, 7 samples (6.306%) were positive. Four positive cases were related to the samples collected in the spring, one was related to the samples collected in the winter, and two were related to the samples collected in the autumn. Conclusion: The contamination rate of Toxocara in stray dogs in Sanandaj is lower than in comparison to the other areas studied in Iran. Given the high number of stray dogs in Sanandaj, it is essential to conduct further eco-epidemiological studies with a focus on dog-borne diseases to determine the importance of stray dogs in transmitting these diseases to humans.